Adjuvant melatonin for uveal melanoma (AMUM): protocol for a randomized open-label phase III study - Ruba Kal Omar; Anna Hagström; Gustav Stålhammar (Trials, 2023)
Abstract Background Uveal melanoma is the most common primary intraocular tumor in adults. In Sweden, at least 100 patients are diagnosed with the disease each year. Almost half of the patients develop metastases, with a median survival time of 1 year once metastases are detected. The primary ocular tumor is typically treated with either enucleation or brachytherapy, and no adjuvant treatment is added. Melatonin is an indolamine hormone that has improved survival in previous trials with patients diagnosed with various cancers, including advanced cutaneous melanoma. Side effects have been mild. We aim to investigate if adjuvant treatment with melatonin for 5 years following diagnosis of non-metastasized uveal melanoma can decrease the occurrence of metastases. Methods An open-label, prospective, 5-year randomized clinical trial (RCT) will be conducted at St. Erik Eye Hospital. One hundred patients recently diagnosed with non-metastatic uveal melanoma will be randomized to either treatment with adjuvant melatonin 20 mg (4 tablets of 5 mg) at 10 pm for 5 years, or to standard follow-up (control group). The primary outcome measurement is the relative risk for having developed metastases 5 years after randomization. The secondary outcomes are overall survival, risk of developing other cancers, overall survival after detection of metastases, and differences in the occurrence of adverse events (AE) and serious adverse events (SAE) between the groups. Discussion Melatonin has been found to positively impact our immune system, inhibit angiogenesis, stimulate apoptosis in malignant cells, and act as a potent antioxidant. Previous clinical trials have used similar doses of melatonin with positive results, particularly in advanced stages of cancer. Previous animal and human studies have found the toxicity of the hormone to be low. Considering the potential benefits and limited risks of melatonin, as well as its global availability, it may be a suitable candidate for an adjuvant treatment in patients with uveal melanoma. Trial registration Our trial protocol has been approved and registered by the Swedish Medical Products Agency on June 22, 2022 (EudraCT 2022–500,307-49–00). Our trial registration number is NCT05502900, and the date of registration is August 16, 2022.